(untitled) (Research, Society and Development, 2022)
Skin cancer is caused by the abnormal and uncontrolled growth of cells that make up the skin and affects thousands of people each year in Brazil. Studies show that the chances of developing skin cancer are reduced if care with sun exposure is adopted since childhood. Therefore, the objective of this study was to analyze the possible contributions of the use of different pedagogical resources related to the teaching of skin cancer among elementary school students from three public schools in the central region of the state of RS. A total of 139 students aged between 8 and 13 years old participated in the research. The pedagogical resources used to carry out the workshops were a booklet, a folder and a flyer, with illustrations and activities about skin cancer and their prevention. The data collection instruments were the field diary and the semi-structured interview. Data treatment was based on content analysis and descriptive statistics. It was observed that the pedagogical resources used aroused students’ interest in learning about the proposed topic and were efficient to start the scientific literacy process related to skin functions, development of skin cancer and factors that influence its emergence appearance. It is believed that these resources contemplated the first structuring axis of scientific literacy, which refers to the basic understanding of terms, knowledge and concepts that lead the student to understand scientific ideas in order to meaning to them in their daily lives.